Characterization of novel antibodies and glycan binding proteins against cancer - Costa, Tiago José Alexandre da Silva (2018)
Cancer is the largest cause of death worldwide and it is increasingly urgent to develop new approaches to diagnosis and therapy. The glycosylation pattern of the cancer cells differ from that of healthy cells and therefore the aberrant expression of glycans are promising targets for diagnosis and therapy. Sialyl-Tn (STn) is a glycan, whose expression is increased in cancer cells and almost absent in normal cells. It is involved in processes such as cancer growth, progression and metastasis. In addition to STn other glycans present an aberrant pattern in cancer. As is the case of Sialyl Lewis X (sLeX) shown overexpressed in tumors. The objective of this work consisted in the characterization of monoclonal antibodies against STn and sLeX produced through the hybridoma technology. The antibodies’ affinity and specificity were tested by flow cytometry and ELISA. In case of STn, different batches of a L2A5 antibody were tested. To select and isolate a better performant hybridoma the original L2A5 hybridoma population was subcloned. Cancer cell lines expressing STn and bovine submaxillary mucins expressing STn, were used for screening by flow cytometry and ELISA, respectively. Both techniques showed that the antibodies produced by the L2A5 hybridoma had affinity and specificity for STn, although these were slightly different between batches. We then cloned the hybridoma cells by limiting dilution. The results allowed selecting the subclone 4E11 which produce antibody with the optimized characteristics. In case of sLeX, a novel antibody is being developed by immunizing mice with glycoproteins carrying sLeX. Mice serum was screened by ELISA and results showed the presence of sLeX-recognizing antibodies. Then the supernatants of hybridomas were screened by ELISA to select those producing a candidate monoclonal antibody that recognize sLeX . Both studies have contributed to the development of new monoclonal antibodies with potential use in the diagnosis and treatment of cancer.